Prevalence and impact of chronic dysglycemia in intensive care unit patients—A retrospective cohort study. Issue 1 (16th September 2020) - Balintescu, Anca; Palmgren, Ida; Lipcsey, Miklós; Oldner, Anders; Larsson, Anders; Cronhjort, Maria; Lind, Marcus; Wernerman, Jan; Mårtensson, Johan
Abstract : Background: The prevalence of chronic dysglycemia (diabetes and prediabetes) in patients admitted to Swedish intensive care units (ICUs) is unknown. We aimed to determine the prevalence of such chronic dysglycemia and asses its impact on blood glucose control and patient‐centered outcomes in critically ill patients. Methods: In this retrospective observational cohort study, we obtained glycated hemoglobin A1c (HbA1c) in patients admitted to four tertiary ICUs in Sweden between March and August 2016. Based on previous diabetes history and HbA1c we determined the prevalence of chronic dysglycemia. We used multivariable regression analyses to study the association of chronic dysglycemia with the time‐weighted average blood glucose concentration, glycemic lability index (GLI), and development of hypoglycemia (co‐primary outcomes), and with ICU length of stay, mechanical ventilation duration, renal replacement therapy (RRT) use, vasopressor use, ICU‐acquired infections, and mortality (exploratory clinical outcomes). Results: Of 943 patients, 312 (33%) had chronic dysglycemia. Of these 312 patients, 84 (27%) had prediabetes, 43 (14%) had undiagnosed diabetes and 185 (59%) had known diabetes. Chronic dysglycemia was independently associated with higher time‐weighted average blood glucose concentration ( P  < .001), higher GLI ( P  < .001), and hypoglycemia ( P  < .001). Chronic dysglycemia was independently associated with RRT use (adjusted odds ratio 1.97, 95% CI 1.24‐3.13, P  = .004) but not with other exploratory clinical outcomes. Conclusions: In four tertiary Swedish ICUs, measurement of HbA1c showed that one‐third of patients had chronic dysglycemia. Chronic dysglycemia was associated with marked derangements in glycemic control, and a greater need for renal replacement therapy.